2022
DOI: 10.3390/tropicalmed8010006
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira borgpetersenii Leucine-Rich Repeat Proteins Provide Strong Protective Efficacy as Novel Leptospiral Vaccine Candidates

Abstract: Leucine-rich repeat (LRR) proteins are advocated for being assessed in vaccine development. Leptospiral LRR proteins were identified recently in silico from the genome of Leptospira borgpetersenii serogroup Sejroe, the seroprevalence of leptospiral infections of cattle in Thailand. Two LRR recombinant proteins, rKU_Sej_LRR_2012M (2012) and rhKU_Sej_LRR_2271 (2271), containing predicted immunogenic epitopes, were investigated for their cross-protective efficacies in an acute leptospirosis model with heterologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In our study MCP antigen elicited significant IgG antibody levels in immunized C3H/HeJ mice, predominantly IgG1 and IgG2a isotypes but minimal IgG3, despite the lack of protection. Factors associated with correlates of protection are still unknown in cases of leptospirosis (17,19,21,22,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). In fact, our study reinforces the need to improve our understanding of the protective immune responses against leptospirosis, especially the role of cellular immune response, which is poorly evaluated in experimental vaccines tested in the hamster model.…”
Section: Discussionmentioning
confidence: 52%
“…In our study MCP antigen elicited significant IgG antibody levels in immunized C3H/HeJ mice, predominantly IgG1 and IgG2a isotypes but minimal IgG3, despite the lack of protection. Factors associated with correlates of protection are still unknown in cases of leptospirosis (17,19,21,22,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). In fact, our study reinforces the need to improve our understanding of the protective immune responses against leptospirosis, especially the role of cellular immune response, which is poorly evaluated in experimental vaccines tested in the hamster model.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, in Bacteroides forsythus, the BspA protein has been postulated as a target for the host immune response 95 . In the case of the bacteria Leptospira borgpetersenii, the recombinant modified leucine-rich repeat protein rhKU_Sej_LRR_2271 has been suggested as a candidate for leptospiral vaccine development 96 . Finally, the same recombinant protein was used to develop a lateral flow strip test for the detection of anti-leptospiral IgG in dogs 97 .…”
Section: Discussionmentioning
confidence: 99%
“…In silico studies, two Leptospira LRR proteins, rKU_Sej_LRR_2012M (LRR2012) and rKU_Sej_LRR_2271 (LRR2271) from L. borgpetersenii were identified and subsequently tested in a hamster model 155 . The study observed that 50% of animals immunized with LRR2012 and 75% of animals immunized with LRR2271 recombinant proteins were protected when challenged with Pomona serovar.…”
Section: Development Of Leptospirosis Vaccinesmentioning
confidence: 99%
“…The study observed that 50% of animals immunized with LRR2012 and 75% of animals immunized with LRR2271 recombinant proteins were protected when challenged with Pomona serovar. In addition, the LRR2271 protein induced a strong humoral response and activated the expression of cytokine genes related to Th1 and Th2 responses 155 …”
Section: Development Of Leptospirosis Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation